2010
DOI: 10.1136/bjo.2009.158261
|View full text |Cite
|
Sign up to set email alerts
|

Little evidence for association of the glaucoma gene MYOC with open-angle glaucoma

Abstract: Background/aimTo determine if overexpression of the glaucoma gene MYOC is involved in the development of open-angle glaucoma (OAG) and if its promoter variants are associated with glaucoma in the Korean population.MethodsHuman trabecular meshwork cells were cultured in the presence of ophthalmic steroids such as fluorometholone, fluorometholone acetate, dexamethasone, prednisolone acetate and rimexolone. The cells were cultured at a hydrostatic pressure of 32 mm Hg above atmospheric pressure and induction of M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 16 publications
0
3
0
1
Order By: Relevance
“…Cells have been treated with a number of steroids including dexamethasone, triamcinolone, prednisolone, cortisol, progesterone, cortexolone, methyltestosterone, fluorometholone, and rimexolone (for examples see (Clark et al, 1994; Raghunathan et al, 2015; Sharma et al, 2014; Sohn et al, 2010)).…”
Section: Ex-vivo Model Systemsmentioning
confidence: 99%
“…Cells have been treated with a number of steroids including dexamethasone, triamcinolone, prednisolone, cortisol, progesterone, cortexolone, methyltestosterone, fluorometholone, and rimexolone (for examples see (Clark et al, 1994; Raghunathan et al, 2015; Sharma et al, 2014; Sohn et al, 2010)).…”
Section: Ex-vivo Model Systemsmentioning
confidence: 99%
“…A more than 100-fold increase in myocilin gene expression has been reported after exposure to dexamethasone [121] . However, a recent study of human trabecular meshwork cells that were cultured in the presence of ophthalmic steroids did not show that myocilin gene overexpression is associated with an increase in IOP [122] . More studies are needed to explain the variations in the myocilin gene and their role in steroid-induced glaucoma.…”
Section: Gene Expressionmentioning
confidence: 99%
“…Supporting the findings of the present study, Rezaie et al ( 10 ) suggested that mutations in OPTN may be responsible for 16.7% of the hereditary forms of NTG and that there is an additional risk factor of 13.6% in familial and sporadic cases. Furthermore, Sohn et al ( 35 ) demonstrated that the MYOC gene itself was not associated with OAG, including POAG, NTG and SIG. Their results do not support the hypothesis that MYOC induction may be linked to IOP variation and that promoter variants of MYOC may be a risk factor for the pathogenesis of OAG.…”
Section: Discussionmentioning
confidence: 99%